Diversidade de parasitos de peixes e sua relação com características dos hospedeiros e do ambiente nos estuários do Rio Mamanguape e Paraíba do Norte, Paraíba, Brasil - Golzio, Jéssica Emília Sérgio de Aquíno (2016)
Reduce human impacts to water quality, potentially affecting biodiversity. Fish parasites can be good indicators of the quality of water bodies, and their presence or absence can be interpreted as a sign of changes in habitat and help in the diagnosis of environmental problems. The study was conducted in two Paraiba’s estuaries, Mamanguape (APA) and North Paraíba (surrounded by riverside community) in order to verify characteristics of the hosts and abiotic data as predictors of wealth gill parasites of fish. The species chosen hosts were Anchoa januaria (Steindachner, 1879), Atherinella brasiliensis (Quoy & Gaimard, 1825), Mugil curema Valenciennes, 1836 and Rhinosardinea bahiensis (Steindachner, 1879). In addition, the most prevalent and abundant copepod, Acusicola brasiliensis, was tested as a possible biomarker. Generalized Linear Models were built with the intention to test the influence of the following predictor variables: weight, length, relative condition factor (Kn) collection period (full or dry), the estuary area, estuary, pH, ammonia, total dissolved solids , turbidity, transparency, nitrate, nitrite, conductivity, total phosphorus and chlorophyll a in wealth response variables of parasites and plenty of Acusicola brasiliensis. Both the wealth and the abundance of A. brasiliensis had significant relationship with parameters that indicate the quality of water, and you can use them as indicators of environmental health.